Data sharing and interoperability in HBIM applied to the Rame Tower - Josefina García-León; Patrizia Murrieri; Manuel Torres Picazo (Disegnare con)
Together with the gradual spread of BIM in the AECO industry, the concept of open BIM began to take root. Semantically HBIM has demonstrated its ability to dialogue with a wide range of stakeholders though multiple visualization and representation tools. But to be able to apply them from the perspective of interoperability among all the professionals, it is necessary to work with standards. For this reason, there has been a growing interest in HBIM, but the process requires specialized standards, today there are only a few recommendations. The bSDD allows linking between all the content inside the database. It provides a standardised workflow to guarantee data quality and information consistency. Projects must be based on openBIM methodologies, using only open, non-proprietary standards and formats, to guarantee an interoperable and collaborative workflow. It has been applied to the Rame Tower, a pre-16th century cultural heritage site, and a characterisation has been achieved based on an international standard language that is interoperable, allowing all stakeholders to share and exchange information about the objects and their properties, increasing the future possibilities for coordination and collaboration throughout the life cycle of the asset. The Digital Twin obtained through this HBIM modelling process is fully dynamic, sharable, and usable in all phases of the asset’s life cycle, and the characterisation and codification based on the interrelation between IFC and bSDD makes the project fully open and sharable. In addition the incorporation of blockchain technology together with HBIM helps to improve aspects such as: authorship and traceability of processes, metadata registration and quality in the creation phases among others. DOI: https://doi.org/10.20365/disegnarecon.32.2024.16